2014
DOI: 10.1590/1982-0216201412413
|View full text |Cite
|
Sign up to set email alerts
|

Mastigação habitual e atividade eletromiográfica dos músculos masseter e temporal em escolares de 7 a 12 anos

Abstract: Conflict of interest: non-existent stimulation of supporting structures, such as bones and teeth and for favoring that the harmonious craniofacial growth occurs³ .The chewing pattern can be influenced by several factors, such as occlusal interferences, dental and/ or periodontal problems, tooth loss, muscle and/or temporomandibular joints problems².It is known that in a unilateral mastication, the chewing muscles are mainly characterized by increased muscle strength on the working side, in other words, where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…The results characterization regarding the mastication preference showed that most children presented a preferential side during usual mastication, agreeing with other researches 11,16,26 . Other studies indicated predominance of bilateral mastication [12][13][14]17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results characterization regarding the mastication preference showed that most children presented a preferential side during usual mastication, agreeing with other researches 11,16,26 . Other studies indicated predominance of bilateral mastication [12][13][14]17 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies about the mastication function in children present data about the side of preferential mastication [12][13][14][15][16] , proprioception (escape of food) 15 , way of incision 15 , lips posture 12,14,15,17 , participation of perioral musculature 12,14,17 and predominant mandibular movement 12,14,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Independente da classificação do estado nutricional, a maioria das crianças apresentou uma mastigação unilateral, assim como identificado por Garcia et al 14 Não houve a presença de ruídos durante o consumo dos alimentos avaliados neste estudo, diferindo daquele realizado com acadêmicos do Curso de Nutrição, em que 6,70% apresentaram ruídos durante o consumo do pão de sal 10 .…”
Section: Resultsunclassified
“…Christensen & Radue [57] analyzed the relation between the side of mastication preference and the dominant hand, but did not find a significant relation. García et al [58] reported that the choice of one of these patterns is influenced by the consistency of the food. Paphangkorakit et al [59] indicated that when a concerted effort is required to cut and grind the food, subjects have a side of preference (for example with pork), whereas with more fragile foods (almonds) they tend toward bilateral mastication.…”
Section: Masticatory Cyclesmentioning
confidence: 99%